SP0152 Learning from clinical trials in systemic lupus erythematosus. (15th June 2017) - Isenberg, DA
Abstract : An enormous sense of frustration has surrounded the results of clinical trials in patients with systemic lupus erythematosus (SLE). A steady stream of trials including those studying the effects of Epratuzumab, Abatacept, Rituximab, Tabalumab and Silfalimumab have failed to meet their endpoints. Even though Benlysta (which blocks the B-cell activating factor BAFF) did meet its endpoints, it only demonstrated a difference of around 10% between the Benlysta-treated and placebo-treated arms in trials involving over 800 patients. However, there are some bright spots on the horizon. Trials comparing the use of Mycophenolate with other classic immunosuppressive drugs clearly showed it to be as good as Cyclophosphamide in getting patients into renal remission and demonstrated its superiority in maintaining that remission compared to Azathioprine (1) . The use of Atacicept which blocks two B-cell activating factors has shown some extremely promising results (2) as have trials of both Rontalizumab and Anifrolumab (3) (which block interferon-alpha). Some key messages learnt from the running of the lupus trials include the importance of minimising the concomitant steroids and immunosuppression; ensuring the quality of those assessors participating in the clinical trials and the utility of employing an independent peer-review panel to monitor data as it is collected from the participating centres during the course of the trial. It is also evident that selecting patients who are more serologically active is likely to be of benefit both in clinical trials and in the clinic. However, we still need better biomarkers to help guide us; the identification of individuals expressing a high interferon alpha signature (and who thus might better benefit from an interferon alpha blocker) is one such example. It remains ironic that Rituximab, the most widely used monoclonal antibody in SLE, failed its endpoint in two clinical trials. However, detailed analyses of data from those trials have shown some encouraging trends including falls in dsDNA antibodies and improvement in some clinical parameters. References: Dooley MA et al. N Engl J Med 2011; 365; 188. Isenberg et al. Ann Rheum Dis 2015; 74; 2006–18. Furie R et al. Arthritis Rheum 2015; 67 (suppl 10) (abstract). Disclosure of Interest: None declared